Solving degree-constrained multicast routing problem by a heuristic genetic algorithm - PAN Yun1; WANG Xing-gang2; FENG Yan-li3; YU Zhen-wei4 (Tongxin xuebao)
With the purpose to solve the degree constrained multicast routing model efficiently,the evolutionary strategy was introduced into heuristic search methods by employing the chromosome as the heuristic information for global searching,and then a hybrid genetic algorithm was proposed.The algorithm not only avoids the difficulty of coding for multicast trees,but also possesses fast convergency and global optimizing capability.Meanwhile,the efficiency of the method is supported by a great number of numerical experiments.